Effectiveness of the Reading, Answering, Discussing, Explaining, and Creating (RADEC) Learning Model in Improving High School Students' Critical Thinking Skills on Colloid Material - Fatimah, Neni Hasnah; Usman, Usman; Sukemi, Sukemi (Jambura Journal of Educational Chemistry, 2024)
Students need to be able to think critically in order to meet the challenges of the 21st century. Be that as it may, the decisive reasoning abilities of understudies are still somewhat low. The RADEC model is a learning model that can aid in the development of critical thinking abilities. The goal of this study is to find out how well the RADEC model helps students in high school think critically about colloidal materials. This study employs experimental, quantitative research techniques. The populace is all understudies in class XI MIPA at SMAN 5 Samarinda. The examples were understudies from class XI MIPA 2 and XI MIPA 4 at SMAN 5 Samarinda, adding up to 75 individuals. The exploration test was chosen utilizing a group irregular inspecting strategy. One-group pre-test post-test design was utilized in the research design. Information assortment involves tests as pre-tests and post-tests, educator and understudy movement perception sheets, and understudy reaction surveys. Statistical tests were conducted first, including the N-Gain test and the effect size test, for data analysis. According to the findings of the research, the RADEC model meets the effective criteria in terms of students' responses to learning based on the RADEC learning model and their increased critical thinking abilities. The findings of the research lead us to the conclusion that the RADEC model works to improve students' critical thinking abilities.